UJI KONSORSIUM EMPAT JAMUR ENDOFIT TANAMAN SAGU TERHADAP COLLETOTRICHUM CAPSICI PADA BUAH CABAI MERAH - Muhammad Ali; Yunel Venita; Martania Natasya Sinaga (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2023)
Colletotrichum capsici is the cause of anthracnose disease on red chili plants that causes a significant decrease chili production in Riau Province. One of the control techniques that can be applied is biological control using endophytic fungi isolated from plants, including sago plants. This study aims to evaluate the consortium of four endophytic isolates of sago plants and to obtain the best consortium of endophytic isolates in inhibiting the fungus, C. capsici which causes anthracnose disease on red chili. This research was carried out at the Plant Disease Laboratory, Faculty of Agriculture, Riau University from June to September 2021. The research was carried out experimentally using a completely randomized design. Four isolates TRA (Trichoderma sp. from root), TRP (Trichoderma sp. from leaf), TRB (Trichoderma sp. from stems) and TV (Thielaviopsis sp.) were compatible and could be consorted. Consortium of TRP+TV, TRA+TRB+TV, TRA+TV, TRB+TV and TRA+TRP+TRB+TV had the ability to inhibit the growth of the fungus C. capsici on PDA medium. Consortium TRP+TV had the highest inhibition potency to C. capsici, which was 61.67%. Consortium TRB+TV had the best ability to delay the initial emergence of disease symptoms and to decrease the disease intensity on red chilli fruits, which was 29.67%.